NIMS: MK Chocotub / Muhammad Kamal Ariffin Jamalluddin and Muhammad Muizzuddin Mohammad Mukhlis - Jamalluddin, Muhammad Kamal Ariffin; Mohammad Mukhlis, Muhammad Muizzuddin (2022)
MK Chocotub is a sub business under Nims Chocotub and based on Shah Alam, Selangor. This business sells product call Crispy Choco Tub and well-known product in 21st century. It is because the product is a chocolate-based cereal in a tub. This brand start with the name Crispy Choco Jar because the origin is in the jar and 2 years later, the brand change into Crispy Choco Tub. This business is sole proprietorship and selling product as main activities. This business sells a total of 6 variety of chocotub starting from RM13-RM16. The ingredients use only premium chocolate and selected cereals. The platform that we use to promote this project using Facebook Page. By promoting in Facebook Page, we are using 3 main elements to promote our business which is teaser, copywriting hard sells and copywriting soft sells. Last but not least, our sales report was attaching as a prove of our selling activities. For this project, both of us have bought 5 tubs of Crispy Choco Tub from the stockist and were sold out, bringing the total sales to RM74. As a result, there is no remaining Crispy Choco Tubs stock.